Lecturers’ Perceptions on the Use of Metacognitive Strategies in Teaching Listening - Putri, Aulia; Eriyanti, Ribut Wahyu; Asih, Ria Arista (Lectura : Jurnal Pendidikan, 2024)
Various strategies can be used for teaching listening. Some lecturers have applied metacognitive strategies in their teaching-learning process to help their students comprehend listening skills. This research aims to examine lecturers’ perceptions of how they use metacognitive strategies in teaching listening. Moreover, this research employed a qualitative methodology. The instrument used was an interview consisting of 7 questions related to how well the lecturers were familiar with metacognitive strategies and how they helped their students in using them in their listening class. Furthermore, the sampling technique used was purposive sampling with the targeted participants who had experience in teaching listening as lecturers. 13 lecturers participated in this research. Then, the data were thematically analyzed. The results showed that the lecturers—called participants thought that it was important to have before, during, and after listening activities to support students absorbed how to think about their thinking process. In addition, the result also found that all of the lecturers had not followed any specific training about how to apply metacognitive strategies in listening class. From the result of the research, it can be concluded that the lecturers think that metacognitive strategies can provide more assistance to students to enhance their listening skills.